How do policy approaches affect refugee economic outcomes? Insights from studies of Syrian refugees in Jordan and Lebanon. (15th September 2022) - Krafft, Caroline; Malaeb, Bilal; Al Zoubi, Saja
Abstract: The vast majority of refugees globally are hosted in developing countries. In Jordan and Lebanon, nearly one in ten people are refugees. This paper reviews how different policy environments in Jordan and Lebanon have shaped economic outcomes for Syrian refugees, focusing on education, work, social assistance, and welfare outcomes. The review summarizes key research on how to improve refugee economic outcomes. We demonstrate that there can be effective service delivery for refugees, dependent on state capacity. For example, differences in policy led to better education outcomes for Syrian refugees in Jordan than in Lebanon. A variety of interventions can support refugee livelihoods, while generally doing no harm to host communities. Both countries also demonstrate the difficulties of achieving refugee economic self-sufficiency. Although Jordan has allowed (limited) legal work opportunities for refugees, Syrian refugees in both countries remain primarily in precarious work and supported by international aid.